Ellen and creative relations - Christoffersen, Erik Exe (Peripeti, 2017)
Ellen (2010) comprises two different kinds of theater. It was played in five different towns and changed from town to town by involving local guests and what was being talked about locally. One part was a careful staging of a new text by the poet Morten Søndergaard, whose poetry paraphrases the name Ellen. Through binaural headphones the audience listens to the recitation of text as well as the precisely choreographed rhythms and directed gazes of the three actors. In the second part 3-4 guests participate from each town. From Silkeborg an interior designer, from Svendborg a hotel director, etc. The guest sequences were set to last some 6 minutes for each guest. To some extent this was prepared, but not rehearsed. In the part without headphones actors interviewed the guests and talked about what the actors had discovered about the town. In this chapter we will shed light on a theater production as a collective production containing a variety of creative individuals and creative strategies.